Development of Some Novel Reverse Transcriptase Inhibitor - Bapna, Mayank; Nema, R.K. (Asian Journal of Chemistry, 2010)
In the present study, a series of substituted 2-aminodarylpyrimidine derivatives were synthesized using Schotten- Bauman and Baker-Venkatraman rearrangement principle followed by cyclization of the obtained product. The formed derivatives were characterized by spectral analysis and the purity was checked by TLC.